Small leucine-rich proteoglycans (SLRPs) in the endometrium of polycystic ovary syndrome women: a pilot study - Ricardo Santos Simões; José Maria Soares-Jr; Manuel J. Simões; Helena B. Nader; Maria Cândida P. Baracat; Gustavo Arantes R. Maciel; Paulo C. Serafini; Ricardo Azziz; Edmund C. Baracat (BMC, 2017)
Abstract Background Small leucine-rich proteoglycans (SLRPs) play an important role in tissue homeostasis and cell proliferation since these proteoglycans sequester multiple growth factors. However, the content of SLRPs in the endometrium of polycystic ovary syndrome (PCOS) women is unknown. Our purpose was to test the hypothesis that excessive endometrial proliferation in PCOS may be partly related to abnormalities in SLRPs. Methods In a cross section study a total of 20 endometrial samples were collected from 10 patients with PCOS and 10 ovulatory women during their proliferative (pre-ovulatory) phase. The study subjects were matched for age, body mass index and race. The age range was 20 to 35 years. All volunteers were evaluated in reproductive endocrinology clinic, Gynecology Division, Clinics Hospital, University of São Paulo Medical School Profile and concentration of small leucine-rich proteoglycans (decorin, lumican, fibromodulin and biglycan) were determined by immunohistochemical testing and Western blotting. Results Decorin and lumican demonstrated higher immunoreactivity and relative expression in the endometrium of women with PCOS compared to that of women with regular menstrual cycles. Conclusion Our data suggests that the endometrium of PCOS women demonstrate a greater content of SLRP than controls; decorin and lumican, in particular, were found in higher concentrations in the endometrium of PCOS women during the proliferative phase. These differences may, in part, explain the excess of endometrial proliferation frequently observed in PCOS. Further studies are warranted.